ШƏКƏРІМ ЖƏНЕ ТОЛСТОЙ. (Eurasian Journal of Philology Science and Education, 2015)
The article is devoted to the problems of literarytranslation in the Kazakh literature.
Keywords: literary translation; Kazakh literature